Pengaruh Keamanan Transaksi Terhadap Kepercayaan Pengguna E-Wallet pada Platform E-Commerce - Putriana, Septi Giseila; Yani, Rika; Putri, Nadia Ega; Maharani, Atika; Puspitasari, Putri; Hawia, Shilvani Laratika; Putri, Liana; Destiarini (ECONOMETRICS:Journal of Sustainable Economics and Management, 2026)
The use of e-wallets in e-commerce transactions continues to increase, but on the other hand it still raises issues related to transaction security and protecting user data privacy. This community service activity is aimed at strengthening the understanding of Shopee users in Baturaja regarding the importance of maintaining account security, protecting personal data, and building a sense of trust when carrying out digital transactions. The aim of this activity is to provide education and assistance so that people are more aware of the risks of data misuse and online fraud. Implementation of activities is carried out through socialization, counseling, interactive discussions, as well as providing educational material to participants. The results of the activity showed that participants experienced an increase in understanding regarding the importance of transaction security and data privacy, accompanied by a change in attitude to being more careful in using e-wallets. Thus, this activity shows that digital education plays an effective role in supporting safer, more comfortable and trustworthy use of e-wallets.